Enchanced Produced Water Treatment Using Zeolite Pretreatment and PVDF-TiO2@UiO-66-NH2 Membrane - Tutuk Djoko Kusworo; Dina Lutfiana Safitri; Meitri Bella Puspa (Diponegoro University, 2026)
Produced water contains complex mixtures of organic and inorganic contaminants that are difficult to remove using conventional treatment methods. This study proposes a hybrid treatment system combining zeolite adsorption as a pretreatment and a PVDF–TiO₂@UiO-66-NH₂ photocatalytic membrane for enhanced produced water purification. The zeolite adsorption process effectively reduced pollutant load prior to membrane filtration, with kinetic analysis indicating that NH₃–N removal followed the pseudo-second-order model (R² ≈ 0.977), suggesting a chemisorption mechanism. Under light irradiation, the photocatalytic membrane demonstrated enhanced performance due to the generation of reactive oxidative species, resulfyting in improved contaminant degradation and flux stability. The optimal membrane (2 wt% TiO₂@UiO-66-NH₂) achieved removal efficiencies of approximately 36% for TDS, 62% for COD, and 80% for NH₃–N. The overall results demonstrate a strong synergistic effect between adsorption, photocatalysis, and membrane filtration, leading to improved treatment efficiency and reduced fouling potential. This integrated approach offers a promising and sustainable solution for produced water treatment.